Pragmatic Analysis of Illocutionary Act Used in Quarrelling Scene of “Ted 2” Movie - Bramantio, Faza Ghalib Miko; Gunawan, Hero (Universitas Galuh, 2025)
This research examines the use of illocutionary speech acts in the quarrelling scenes of the film